163k views
4 votes
g Given the following premises: (1) a∧(b∨a) (2) ~c→~a (3) ~g→~a (4) g→e (5)~(d∨h) Prove the Conclusion: c∧~h?

User Halocursed
by
5.4k points

1 Answer

3 votes

Answer:

See the argument below

Explanation:

I will give the argument in symbolic form, using rules of inference.

First, let's conclude c.

(1)⇒a by simplification of conjunction

a⇒¬(¬a) by double negation

¬(¬a)∧(2)⇒¬(¬c) by Modus tollens

¬(¬c)⇒c by double negation

Now, the premise (5) is equivalent to ¬d∧¬h which is one of De Morgan's laws. From simplification, we conclude ¬h. We also concluded c before, then by adjunction, we conclude c∧¬h.

An alternative approach to De Morgan's law is the following:

By contradiction proof, assume h is true.

h⇒d∨h by addition

(5)∧(d∨h)⇒¬(d∨h)∧(d∨h), a contradiction. Hence we conclude ¬h.

User Moniquea
by
6.3k points